Letrozole, for the Management of Chronic Pelvic Pain Resulting from Endometriosis - Quratulain Qureshi, Muneeba Sadaf, Rukhsana, Rubina Amjad, Anita Dileep, Muhammad Parial Shahani, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Letrozole, an aromatase inhibitor that inhibits the final step of the estrogen biosynthesis pathway to prevent estrogen synthesis, has been utilized in a variety of infertile scenarios. A common gynecological pain problem called endometriosis involves tissue that resembles the tissue that typically lines the inner layer of the uterus. It frequently results in fertility issues. According to the trials, the Letrozole medication continues to reduce the severity of persistent pelvic pain. According to reports, Letrozole therapy relieves pelvic pain brought on by endometriosis. Objective: In this study, we evaluated Letroszole's effectiveness in treating chronic pelvic discomfort associated with endometriosis. Study Design: A cross-sectional study Place and Duration: This study was conducted at Sandeman Provincial Hospital (SPH) / BMCH, Quetta Pakistan from December 2021 to December 2022. Methodology: A total of 60 patients with endometriosis were taken in this study. Patients with a past history of treatment for endometriosis with varying degrees of improvement were also included. Data was analyzed on SPSS version 24.0. Before starting the treatment, an initial diagnostic laparoscopy was used to diagnose and score endometriosis. Oral administration of Letrozole 2.5mg, celbex 200mg three times a day, calcium citrate 1000 mg, progestin norethisterone acetate 5 mg, and vitamin D (1000 IU) was given for 6 months Results: The mean age of the participants was30.9years. A total of 26 (43.3%) patients presented with dysmenorrhea. Out of 60 patients, 43 (71.6%) were nulliparous. The mean visual analogue scale which was 7.12 at the start of the therapy, dropped to 6.8 (p-value 0.02) in one month and dropped to 3.3 in six months of the therapy. Conclusion: Letrozole has been shown to be effective in treating pelvic pain related to endometriosis, with notable pain reduction and no recurrence of symptoms. Keywords: Letrozole, Endometriosis, pain score